(INVITED)Dispersion-shifted tellurite fibers for nonlinear frequency conversion - M. Evrard; E. Serrano; C. Strutynski; F. Désévédavy; G. Gadret; J.C. Jules; B. Kibler; F. Smektala (Optical Materials: X, 2022)
We report a detailed numerical investigation of step-index tellurite fiber properties based on the careful experimental characterization of refractive indices for two tellurite-glass systems employed in fiber manufacturing. More specifically, our study focuses on two typical step-index configurations, namely weak and strong index differences between core and cladding glasses. We reveal that a wide range of dispersion-shifted features for tellurite fibers can be obtained in the 2–3 μm range combined with small or large effective mode areas. Our work also outlines the potential application of such dispersion-engineered fibers for nonlinear wavelength converters between near- and mid-infrared regions.